Misuse of Village Funds in the Perspective of Village Financial Supervision and Accountability: (Case Study in Mancagar Village, Lebakwangi District, Kuningan Regency) - Gina Nurfaidah; Harmono Harmono (Ann Publisher, 2026)
Background. Village Fund Management is part of public finances and plays an important role in community development and welfare, but remains vulnerable to irregularities due to weak supervision and accountability. Aims. This study aims to identify factors that are obstacles in the supervision of the management of Village Funds, as well as analyze the optimization of the Village Fund supervision mechanism in realizing transparency and accountability. Methods. By using qualitative research methods and empirical juridical approaches. Result. It was found that the misuse of Village Funds is mainly due to weak internal control, lack of guidance and supervision of local governments, low community participation, and dominance of repressive approaches in law enforcement. This condition has implications for the misuse of Village Funds as happened in Mancagar Village, Lebakwangi District, Kuningan Regency. Conclusion. Therefore, it is necessary to optimize the supervision of Village Funds through increasing the capacity of village apparatus, strengthening coaching and supervision by local governments, increasing community participation, optimizing the use of the Siskeudes application, as well as creating village websites and social media, in order to realize transparent and accountable management of Village Funds.